Introducing helmet non-invasive ventilation during COVID-19 pandemic: Early experience of two centres - Chaudhuri, Dipayan; Sharma, Rishi; Burns, Karen E. A.; Piticaru, Joshua; Cook, Deborah J.; Rochwerg, Bram (Frontiers in Medicine, 2023)
Purpose The helmet is a novel interface for delivering non-invasive ventilation (NIV). We conducted a case series to characterize introduction of the helmet interface in both COVID and non-COVID patients at two-centres. Methods We enrolled all patients with respiratory failure admitted to the Juravinski Hospital (Hamilton, Canada) and St. Joseph’s Health Center (Syracuse, New York) between November 1, 2020 and June 30, 2021 who used the helmet interface (Intersurgical StarMed) as part of this introduction into clinical practice. We collected patient demographics, reason for respiratory failure, NIV settings, device-related complications and outcomes. We report respiratory therapist’s initial experiences with the helmet using descriptive results. Results We included 16 patients with a mean age of 64.3 ± 10.9 years. The most common etiology for respiratory failure was pneumonia (81.3%). The median duration of NIV during the ICU admission was 67.5 (15.3, 80.8) hours, with a mean maximum PS of 13.9 ± 6.6 cm H2O and a mean maximum PEEP of 10.4 ± 5.1 cm H20. Three patients (18.7%) did not tolerate the helmet. Ten (62.5%) patients ultimately required intubation, and 7 (43.4%) patients died while in the ICU. The most common reason for intubation was worsening hypoxia (70%). No adverse events related to the helmet were recorded. Conclusion Over the 8-month period of this study, we found that the helmet was well tolerated in over 80% of patients, although, more than half ultimately required intubation. Randomized controlled trials with this device are required to fully assess the efficacy of this interface.